2005
DOI: 10.1007/s00414-005-0012-7
|View full text |Cite
|
Sign up to set email alerts
|

Stability of ethyl glucuronide in urine, post-mortem tissue and blood samples

Abstract: The stability of ethyl glucuronide (EtG) under conditions of degradation was examined in urine samples of nine volunteers and in post-mortem tissue (liver, skeletal muscle) and blood taken from seven corpses at autopsies. Analysis was performed via LC-MS/MS. EtG concentrations in urine samples ranged from 2.5 to 296.5 mg/l. When stored at 4 degrees C in airtight test tubes, EtG concentrations remained relatively constant; when stored at room temperature (RT) for 5 weeks in ventilated vials, variations of EtG c… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
51
4
7

Year Published

2007
2007
2022
2022

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 79 publications
(63 citation statements)
references
References 19 publications
1
51
4
7
Order By: Relevance
“…Both our work (papers II and III) and other studies (115,138) showed that no EtG was formed, while another work (147) showed formation of EtG in clinical urine samples containing bacteria.…”
Section: Use Of Etg and Ets As A Marker Of Ante Mortem Alcohol Ingestmentioning
confidence: 79%
See 2 more Smart Citations
“…Both our work (papers II and III) and other studies (115,138) showed that no EtG was formed, while another work (147) showed formation of EtG in clinical urine samples containing bacteria.…”
Section: Use Of Etg and Ets As A Marker Of Ante Mortem Alcohol Ingestmentioning
confidence: 79%
“…Both our study (paper II) and others have documented that EtG is unstable in the presence of bacteria, both in post mortem material (115,119) and in clinical urine samples (146,147 Weinmann, personal information). We found that refrigeration and the presence of preservatives made EtG stable (paper II), results that are also supported by other publications (146,148).…”
Section: Use Of Etg and Ets As A Marker Of Ante Mortem Alcohol Ingestmentioning
confidence: 99%
See 1 more Smart Citation
“…Schloegl et al [27] examined the stability of EtG in several substrates including urine from volunteers and postmortem specimens. The study was carried out on urine samples of nine volunteers who had consumed different amount of alcohol during the previous evening, stored up to 5 weeks at room temperature and at 4°C.…”
Section: Ethyl Glucuronide and Ethyl Sulphatementioning
confidence: 99%
“…In the interpretation of a postmortem ethanol finding, criteria like specific case information and comparisons of ethanol levels in blood, urine and vitreous humor are often used, but are not always reliable (2,3). A supplementary method to distinguish antemortem ethanol consumption from postmortem ethanol formation is the analysis of the ethanol metabolites ethyl glucuronide (EtG) and ethyl sulfate (EtS) (4)(5)(6)(7). These metabolites are produced by enzymatic conjugation of ethanol in living individuals (8,9).…”
Section: Introductionmentioning
confidence: 99%